COVID-19-associated pulmonary aspergillosis in a Japanese man: A case report. Issue 6 (June 2021) - Imoto, Waki; Himura, Hoshi; Matsuo, Kenji; Kawata, Sae; Kiritoshi, Ayako; Deguchi, Ryo; Miyashita, Masahiro; Kaga, Shinichiro; Noda, Tomohiro; Yamamoto, Katsumi; Yamada, Koichi; Uchida, Kenichiro; et al.
Abstract: CAPA (COVID-19 associated pulmonary aspergillosis) is an important complication of COVID-19. It has been reported that the incidence of CAPA is as high as 19%–33% worldwide. However, its onset has not been reported in Japan. A 72-year-old Japanese man was diagnosed with COVID-19 and was transferred to our hospital due to deterioration of respiratory condition. Treatment with remdesivir, dexamethasone (DEXA), and antibiotics was performed under mechanical ventilation. Although the condition improved temporarily, a new shadow appeared in the lung, and Aspergillus fumigatus was cultured from sputum. The patient was clinically diagnosed with CAPA and treated with voriconazole. However, his progress deteriorated and he died. High-risk COVID-19 patients should be tested for Aspergillus to ensure early diagnosis of CAPA.